Residential noise analysis - Lim, Shawn Wei Kit (Nanyang Technological University, 2024)
Noise pollution, specifically inter-floor noise pollution, has presented itself as a pressing concern in residential buildings, causing reduced quality of life as well as social friction amongst neighbors. This is a result of the rapid urbanization and environmental challenges within our urban landscape. This project aims to cover the complexities of inter-floor noise and its analysis. Examples of inter-floor noise would include impact from basketballs, furniture movement and other structural or household vibrations and noises. Through the usage of vibration sensors and the analysis of the acoustical data captured, the noise types and their respective characteristics are captured and carefully interpreted. Earlier research teams have gathered some pertinent data, which will be leveraged upon in this project for the purposes of processing, synchronizing and analyzing the raw acoustical information. Some areas of focus within this project would be the data conversion and sanitization as well as deep analysis using advanced software such as MATLAB, ArtemiS Suite version 11, Audacity and Excel Workbook.